Crossovers: Digitalization and literature in foreign language education - Lütge, Christiane; Merse, Thorsten; Owczarek, Claudia; Stannard, Michelle (Studies in Second Language Learning and Teaching, 2019)
Digitalization produces increasingly multimodal and interactive literary forms. A major challenge for foreign language education in adopting such forms lies in deconstructing discursive borders between literary education and digital education (romance of the book vs. euphoric media heavens), thereby crossing over into a perspective in which digital and literary education are intertwined. In engaging with digital literary texts, it is additionally important to consider how different competencies and literary/literacy practices interact and inform each other, including: (1) a receptive perspective: reading digital narratives and digital literature can become a space for literary aesthetic experience, and (2) a productive perspective: learners can become “produsers” (Bruns, 2008) of their own digital narratives by drawing on existing genre conventions and redesigning “available designs” (New London Group, 1996). Consequently, we propose a typology of digital literatures, incorporating functional, interactive and narrative aspects, as applied to a diverse range of digital texts. To further support our discussion, we draw on a range of international studies in the fields of literacies education and 21st century literatures (e.g., Beavis, 2010; Hammond, 2016; Kalantzis & Cope, 2012; Ryan, 2015) and, in turn, explore trajectories for using concrete digital literary texts in the foreign language classroom.